Safety and efficacy of 3‐phytase FLF1000 as a feed additive for chickens for fattening and laying hens. (29th November 2016) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; de Lourdes Bastos, Maria; Bories, Georges; Chesson, Andrew; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; Kouba, Maryline; et al.
Abstract: The additive is a preparation of 3‐phytase which is produced by a genetically modified strain of Komagataella pastoris . The production strain and its recombinant DNA were not detected in the final product. Therefore, the additive does not give rise to safety concerns with regard to the genetic modification of the production strain. Based on the results of the tolerance studies provided, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive is safe for chickens for fattening and laying hens at the dose of 1, 000 FTU/kg feed. However, a margin of safety could not be established for laying hens. The production strain belongs to a species considered to qualify for the qualified presumption of safety (QPS) approach to safety assessment when used for enzyme production. Since the identity of the strain was unambiguously established and the genetic modification raised no concerns, the FEEDAP Panel concludes that the use of the additive as a feed additive is of no concerns for consumers. The additive is not an irritant to eyes and skin, and it is not a dermal sensitiser. Owing to the proteinaceous nature of the active substance, the additive is a potential respiratory sensitiser, however, exposure may be limited. The use of the product as a feed additive does not pose risks to the environment. The Panel concluded that the additive has a potential to increase the availability of phytate phosphorus in chickens for fattening at 500 FTU/kg and in laying hens at 1, 000 FTU/kg feed.